Neuroprotective efficacy and therapeutic window of curcuma oil: in rat embolic stroke model - Jagannathan NR; sharma Uma; Garg Puja; Dohare Preeti; Ray Madhur (BMC, 2008)
Abstract Background Among the naturally occurring compounds, turmeric from the dried rhizome of the plant Curcuma longa has long been used extensively as a condiment and a household remedy all over Southeast Asia. Turmeric contains essential oil, yellow pigments (curcuminoids), starch and oleoresin. The present study was designed for investigating the neuroprotective efficacy and the time window for effective therapeutic use of Curcuma oil (C. oil). Method In the present study, the effect of post ischemic treatment of C.oil after ischemia induced by occlusion of the middle cerebral artery in the rat was observed. C.oil (500 mg/kg body wt) was given 4 hrs post ischemia. The significant effect on lesion size as visualized by using diffusion-weighted magnetic resonance imaging and neuroscore was still evident when treatment was started 4 hours after insult. Animals were assessed for behavioral deficit scores after 5 and 24 hours of ischemia. Subsequently, the rats were sacrificed for evaluation of infarct and edema volumes and other parameters. Results C.oil ameliorated the ischemia induced neurological functional deficits and the infarct and edema volumes measured after 5 and 24 hrs of ischemia. After 24 hrs, immunohistochemical and Western blot analysis demonstrated that the expression of iNOS, cytochrome c and Bax/Bcl-2 were altered after the insult, and antagonized by treatment with C.oil. C.oil significantly reduced nitrosative stress, tended to correct the decreased mitochondrial membrane potential, and also affected caspase-3 activation finally apoptosis. Conclusion Here we demonstrated that iNOS-derived NO produced during ischemic injury was crucial for the up-regulation of ischemic injury targets. C.oil down-regulates these targets this coincided with an increased survival rate of neurons.